Alkaline ribonuclease activity in maternal serum and in serum of newborns from birth up to thirty days of age. A study made with full-term appropriate-, full-term small- and preterm appropriate-for-gestational-age infants - Trindade, C. E P; de Nobrega, F. J.; Sartor, M. E A; Suguihara, C. Y.; Tonete, S. S.; Curi, P. (Karger Publishers, 1985)
We have studied the alkaline ribonuclease (RNase) activity in maternal serum and serum of full-term small- (T-SGA), full-term appropriate- (T-AGA) and preterm appropriate-for-gestational age (PT-AGA) newborns. A significantly lower level of RNase was observed in T-AGA and T-SGA newborns on the 30th day of age and in PT-AGA newborns on the 15th and 30th days of age, as compared to other T-AGA, T-SGA and PT-AGA groups of infants at birth. RNase activity was significantly higher in cord blood than in the maternal blood in all categories studied. Moreover, in preterm newborns, RNase activity in cord blood was significantly higher in those presenting a lower gestational age. We did not observe any significant difference in RNase levels in the cord blood of newborns from the 3 categories studied. The same results were observed concerning maternal blood. We, therefore, conclude that RNase activity in cord blood or in maternal blood is not a very statisfactory indicator of fetal malnutrition.
Keywords: pancreatic ribonuclease; adult; age; blood and hemopoietic system; classification; diagnosis; fetus; human; intrauterine growth retardation; low birth weight; maternal blood; newborn; pregnancy; prematurity; priority journal; umbilical cord blood; Female; Fetal Blood; Fetal Growth Retardation; Humans; Infant, Newborn; Infant, Premature; Infant, Small for Gestational Age; Placental Insufficiency; Pregnancy; Ribonucleases